IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INGGRIS DENGAN METODE BLENDED LEARNING DI SMP SWASTA AL IHSAN MULIA - MEDAN - TITIM ELIAWATI; APRILIA KEMALASARI; EVI MAHARANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This community service activity provides a deep meaning about humans as social beings who sometimes need a social environment, meeting with friends and teachers where learning effectiveness can be achieved with the help of others around us. This community service activity has the theme